The Translation of School Based Nutrition into Home Eating Behaviors (OR13-05-19). (13th June 2019) - Weisberg-Shapiro, Pamela; Biancavilla, Victoria; Chan, Camille; Yeh, Tiffany
Abstract: Objectives: The purpose of this study was to assess how a school based nutrition education program in a low-income rural elementary school in upstate New York influenced families' eating behaviors. Methods: Students attending an elementary school in a low-income, rural community in upstate New York attended monthly nutrition education sessions and cooking demonstrations that included child-friendly recipes for fruits and vegetables. Recipes from the cooking demonstration were sent home with the children. In year two and three of the program, twenty caregivers participated in 45–75 qualitative interviews assessing how the program influenced the families' eating behaviors. Interviews were transcribed verbatim and coded in Atlas TI using a grounded theory approach. In addition, the community's food availability was assessed using google maps and ground truthing. Results: Preliminary findings indicate that families did not change their eating behaviors in response to the school based nutrition program. Most parents reported that they received the recipes from school and some reported trying recipes. However, with the exception of one family, overall eating patterns and food routines did not change. Parents who described a low consumption of fruits and vegetables indicated that barriers to incorporating the recipes, and healthy foods in general, into their food routines included perception of children's food preferences, time constraints and financial constraints. Parents who described a high consumption of fruits and vegetables indicated that they did not incorporate recipes into their routines because they already had healthy eating routines. Conclusions: School based programs should engage families in community events and family cooking classes. These events should aim to assist parents in navigating barriers to healthy eating. Funding Sources: Engaged Cornell.